Antimicrobial activity, phytochemical and toxicity analyses of jambu mawar [Syzygium jambos (L.) Alston] leaf extract on shrimp and cherry tomato samples - Ali, Salar Kadhum (2021)
Infections caused by foodborne and waterborne pathogens have brought a serious attention in the last decades. In the last two decades, the discovery and development of new antimicrobial agents have been unprecedented activity. Since most of these antimicrobial agents are not applicable to apply in food productions that led most of the food manufacturers to find the alternative and that is a natural antimicrobial agent, which has no effect on the nutritional and sensory aspect of the foodstuffs and satisfy the consumer demand. Jambu mawar [Syzygium jambos (L.) Alston] is a species of the genus Syzygium, which has belonged to the family of Myrtaceae and has been reported for its medicinal uses as anti-inflammatory, antioxidant, antibacterial and hepatoprotective, and treatment of a variety of illnesses as toothache, diabetes, diuretic, diarrhea, dysentery and leprosy. The objectives of this study were to determine the antimicrobial activity and mechanism of S. jambos (L.) Alston leaf extract against foodborne pathogens namely V. parahaemolyticus ATCC17802, L. monocytogenes ATCC19112, K. pneuomoniae ATCC13773, S. aureus ATCC29737, P. mirabilis ATCC21100 and P. aeruginosa ATCC9027, and food spoilage microorganisms C. albicans ATCC10231, C. krusei ATCC32196, C. glabrata ATCC2001, C. parapsilosis ATCC22019, Asp. fumigatus ATCC26430, Asp. niger ATCC9029, Rh. oligosporus ATCC22959 and Rh. oryzae ATTC 22580, to analyses the phytochemicals, its stability and toxicity of the extract, and to evaluate the effect of the extract on microbial population in food samples. The dried leaf were extracted using ethanol as a solvent with maceration method. Antimicrobial activity against foodborne pathogens were determined using Clinical and Laboratory Standard Institute (CLSI) methods. The stability of antimicrobial activity of the extract was conducted at different pHs and temperatures. Cell constituent release and crystal violet analysis were the methods used to investigate the mechanism of action of the extract. The phytochemicals compounds in the extract were analyzed using GC-MS and LC-MS. The toxicity level of the extract was assessed using brine shrimp lethality assay (Artemia salina spp.). Finally, the effect of the extract on natural microflora populations on shrimp and cherry tomato samples via washing treatment were conducted at different concentrations (0.05, 0.5 and 5%) and soaking time (5 and 15 min), and different storage temperatures. The results showed that the extract can inhibit all microbial tested with inhibition zone ranged between 7.00 ± 0.00 to 10.25 ± 0.29 mm. The minimum inhibitory concentrations (MICs) of the extract were ranged between 0.01 to 2.5 mg/mL, whereas the MB/FC ranged 0.01 to 5.00 mg/mL. Time-kill curve assay demonstrated that all microbial tested can reduced ≥3 Log10 up to 4× MIC for 2 h. Meanwhile, quantitative analysis of conidia inhibition showed all conidia of fungi tested were killed or reduced in the range of 89% to 100% inhibition after 48 h of incubation and no filamentous growth after treated with extract between 0.5× MIC and 2× MIC for 14 days. Cell constituent release and crystal violet analysis of representative pathogens treated with the extract at MIC values showed disruption and leakage of the cell cytoplasm. Generally, the antimicrobial activity of the extract against all tested microorganisms at different pHs (3, 6, 7 and 11) and temperatures (30˚C, 50˚C and 80˚C) was not significantly different, meaning the extract was stable. GC-MS analysis identified the presence of 35 compounds in the extract and the antimicrobial active compounds includes methyl 5,11,14,17-eicosatetraenoate, phytol, ethyl linoleate, phenol, 3-pentadecyl, squalene, 9,12,15-octadecatrienoic acid, methyl ester, neophytadiene, gamma-tocopherol and alpha-amyrin. LC-MS analysis were identified 36 compounds such as ferulic acid, rutin, 3,4-Dihydrocadalene, curcumene, and ethyl myristate. The toxicity analysis of the extract demonstrated that the LC50 was 4.51 mg/mL; it might consider being safe. Syzygium jambos (L.) Alston leaf extract as a washing treatment solution demonstrated a significant reduction of natural microflora in tested food samples were started at 0.05% (v/v) of extract at 15 min. In storage study, 0.5% (v/v) of the extract exhibited a better effect in controlling the microbial survival throughout the storage time. In conclusion, S. jambos (L.) Alston leaf extract exhibits antimicrobial activities against wide spectrum of foodborne pathogens and food spoilage microorganisms with no significant affect by exposure to different pHs and temperatures, and no toxicity effect, thus it can be developed as a natural sanitizer for washing raw food materials.